CORRIGENDUM, Long Term Exposure to Benzo[b]fluoranthene Does Not Induce Mutations in MutaMouse Male Germ Cells. Reprod Toxicol, 2025, 137:108985 http://doi.org/10.1016/j.reprotox.2025.108985 - Madison T. Stewart; Gu Zhou; Danielle P.M. LeBlanc; Annette E. Dodge; Matthew J. Meier; Andrew Williams; Alexandra S. Long; Paul A. White; Carole L. Yauk; Francesco Marchetti (Reproductive Toxicology, 2026)

Potent carbonic anhydrase inhibition by ruthenium(II)-acetazolamide conjugates uncoupled from antiproliferative activity in vitro - Alberto Gobbo; Simone Giovannuzzi; Maria Luisa Massardi; Marta Turati; Lorenzo Biancalana; Stefano Zacchini; Marco Bortoluzzi; Claudiu T. Supuran; Fabio Marchetti (Chemico-Biological Interactions, 2026)

Long term exposure to benzo[b]fluoranthene does not induce mutations in Mutamouse male germ cells - Madison T. Stewart; Gu Zhou; Danielle P.M. LeBlanc; Annette E. Dodge; Matthew J. Meier; Andrew Williams; Alexandra S. Long; Paul A. White; Carole L. Yauk; Francesco Marchetti (Reproductive Toxicology, 2025)

Nourish: The User Experience - M. Hesse; T. Marchetti; J. Walsh; K. Good (Journal of the Academy of Nutrition and Dietetics, 2025)

P09-36 The toxicological effects of ultrafine particles (UFP) resulting from the combustion of fossil-based fuels and bio-fuels in an atmospheric simulation chamber - S. Marchetti; G. Motta; V. Vernocchi; G. De Falco; M. Commodo; A. D'Anna; T. Isolabella; D. Massabò; P. Minutolo; P. Prati; P. Mantecca; M. Gualtieri (Toxicology Letters, 2025)

Corrigendum: Diatom transcriptional and physiological responses to changes in iron bioavailability across ocean provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2025)

Inhalation of nanoplastics in the mouse model: Tissue bio-distribution and effects on the olfactory system - G. Prosperi; N. Marchetti; A. D'Elia; R. Massari; M. Giusto; A. Pietrodangelo; T. Rossi; A. Nucara; F. Scavizzi; G. Strimpakos; S. Marinelli; S. Mandillo; et al. (Science of The Total Environment, 2025)

Variability in the phytoplankton response to upwelling across an iron limitation mosaic within the California current system - YuanYu Lin; Olivia Torano; Logan Whitehouse; Emily Pierce; Claire P. Till; Matthew Hurst; Robert Freiberger; Travis Mellett; Maria T. Maldonado; Jian Guo; Mariam Sutton; David Zeitz; et al. (Limnology and Oceanography, 2024)
Coastal upwelling currents such as the California Current System (CCS) comprise some of the most productive biological systems on the planet. Diatoms dominate these upwelling events in part due to their rapid response to nutrient entrainment. In this region, they may also be limited by the micronutrient iron (Fe), an important trace element primarily involved in photosynthesis and nitrogen assimilation. The mechanisms behind how diatoms physiologically acclimate to the different stages of the upwelling conveyor belt cycle remain largely uncharacterized. Here, we explore their physiological and metatranscriptomic response to the upwelling cycle with respect to the Fe limitation mosaic that exists in the CCS. Subsurface, natural plankton assemblages that would potentially seed surface blooms were examined over wide and narrow shelf regions. The initial biomass and physiological state of the phytoplankton community had a large impact on the overall response to simulated upwelling. Following on‐deck incubations under varying Fe physiological states, our results suggest that diatoms quickly dominated the blooms by “frontloading” nitrogen assimilation genes prior to upwelling. However, diatoms subjected to induced Fe limitation exhibited reductions in carbon and nitrogen uptake and decreasing biomass accumulation. Simultaneously, they exhibited a distinct gene expression response which included increased expression of Fe‐starvation induced proteins and decreased expression of nitrogen assimilation and photosynthesis genes. These findings may have significant implications for upwelling events in future oceans, where changes in ocean conditions are projected to amplify the gradient of Fe limitation in coastal upwelling regions.

A second update to the checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; G. Calvia; et al. (Plant Biosystems, 2024)

A second update to the checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; M. Castello; et al. (Plant Biosystems, 2024)

Evaluation of a long-term information tool reveals continued suitability for identifying bycatch hotspots but little effect on fisher location choice - Zachary A. Siders; Robert N.M. Ahrens; Summer Martin; Edward V. Camp; Alexander R. Gaos; John H. Wang; Jamie Marchetti; T. Todd Jones (Biological Conservation, 2023)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The iron limitation mosaic in the California Current System: Factors governing Fe availability in the shelf/near‐shelf region - C. P. Till; J. R. Solomon; N. R. Cohen; R. H. Lampe; A. Marchetti; T. H. Coale; K. W. Bruland (Limnology and Oceanography, 2019)
The California Current System is a productive eastern boundary region off the coasts of Washington, Oregon, and California. There is strong seasonality to the region, with high levels of rainfall and river input to the coastal ocean during the winter season, and coastal and Ekman upwelling during the spring and summer. Iron (Fe) input to the coastal ocean during the winter months can be stored in the continental shelf mud belts and then be delivered to the surface ocean by upwelling in the spring and summer. There have been a number of studies providing strong evidence of Fe‐limitation of diatom growth occurring in regions of the California Current System off of California, and the occurrence of Fe‐limitation has been linked with narrow continental shelf mud belt width and low river input. We provide evidence for potential Fe‐limitation of diatoms off the southern coast of Oregon in July 2014, just off the shelf break near Cape Blanco in a region with moderate shelf width and river input. Since eastern boundary regions account for a disproportionally large amount of global primary production, this observation of potential Fe‐limitation in an unexpected near‐shore region of the California Current System has implications for global models of primary productivity. In order to re‐evaluate the factors impacting Fe availability, we utilize satellite imagery to compare with historical datasets, and show that unexpected levels of Fe can often be explained by eddies, plumes of upwelled water moving offshore, or lack of recent upwelling.

Divergent gene expression among phytoplankton taxa in response to upwelling - Robert H. Lampe; Natalie R. Cohen; Kelsey A. Ellis; Kenneth W. Bruland; Maria T. Maldonado; Tawnya D. Peterson; Claire P. Till; Mark A. Brzezinski; Sibel Bargu; Kimberlee Thamatrakoln; Fedor I Kuzminov; Benjamin S. Twining; et al. (Environmental Microbiology, 2018)
Summary Frequent blooms of phytoplankton occur in coastal upwelling zones creating hotspots of biological productivity in the ocean. As cold, nutrient‐rich water is brought up to sunlit layers from depth, phytoplankton are also transported upwards to seed surface blooms that are often dominated by diatoms. The physiological response of phytoplankton to this process, commonly referred to as shift‐up, is characterized by increases in nitrate assimilation and rapid growth rates. To examine the molecular underpinnings behind this phenomenon, metatranscriptomics was applied to a simulated upwelling experiment using natural phytoplankton communities from the California Upwelling Zone. An increase in diatom growth following 5 days of incubation was attributed to the genera Chaetoceros and Pseudo‐nitzschia . Here, we show that certain bloom‐forming diatoms exhibit a distinct transcriptional response that coordinates shift‐up where diatoms exhibited the greatest transcriptional change following upwelling; however, comparison of co‐expressed genes exposed overrepresentation of distinct sets within each of the dominant phytoplankton groups. The analysis revealed that diatoms frontload genes involved in nitrogen assimilation likely in order to outcompete other groups for available nitrogen during upwelling events. We speculate that the evolutionary success of diatoms may be due, in part, to this proactive response to frequently encountered changes in their environment.

An updated checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; N. M. G. Ardenghi; E. Banfi; L. Celesti-Grapow; A. Albano; A. Alessandrini; G. Bacchetta; S. Ballelli; M. Bandini Mazzanti; G. Barberis; et al. (Plant Biosystems, 2018)

Corrigendum: Diatom Transcriptional and Physiological Responses to Changes in Iron Bioavailability across Ocean Provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2018)

BacHBerry: BACterial Hosts for production of Bioactive phenolics from bERRY fruits - Alexey Dudnik; A. Filipa Almeida; Ricardo Andrade; Barbara Avila; Pilar Bañados; Diane Barbay; Jean-Etienne Bassard; Mounir Benkoulouche; Michael Bott; Adelaide Braga; Dario Breitel; Rex Brennan; et al. (Phytochemistry Reviews, 2018)

An updated checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Albano; A. Alessandrini; N. M. G. Ardenghi; G. Astuti; G. Bacchetta; S. Ballelli; E. Banfi; G. Barberis; L. Bernardo; et al. (Plant Biosystems, 2018)

Toward an Improved Representation of Middle Atmospheric Dynamics Thanks to the ARISE Project - E. Blanc; L. Ceranna; A. Hauchecorne; A. Charlton-Perez; E. Marchetti; L. G. Evers; T. Kvaerna; J. Lastovicka; L. Eliasson; N. B. Crosby; P. Blanc-Benon; A. Le Pichon; et al. (Surveys in Geophysics, 2018)

Diatom Transcriptional and Physiological Responses to Changes in Iron Bioavailability across Ocean Provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2017)
Changes in iron (Fe) bioavailability influence diatom physiology and community composition, and thus have a profound impact on primary productivity and ecosystem dynamics. Iron limitation of diatom growth rates has been demonstrated in both oceanic and coastal waters of the Northeast Pacific Ocean and is predicted to become more pervasive in future oceans. However, it is unclear how the strategies utilized by phytoplankton to cope with low Fe bioavailability and resupply differ across these ocean provinces. We investigated the response of diatom communities to variable Fe conditions through incubation experiments performed in the Fe mosaic of the California Upwelling Zone and along a natural Fe gradient in the Northeast Pacific Ocean. Through coupling gene expression of two dominant diatom taxa ( Pseudo-nitzschia and Thalassiosira ) with biological rate process measurements, we provide an in-depth examination of the physiological and molecular responses associated with varying Fe status. Following Fe enrichment, oceanic diatoms showed distinct differential expression of gene products involved in nitrogen assimilation, photosynthetic carbon fixation, and vitamin production compared to diatoms from low-Fe coastal sites, possibly driven by the chronic nature of Fe stress at the oceanic site. Genes of interest involved in Fe and N metabolism additionally exhibited divergent expression patterns between the two diatom taxa investigated, demonstrating that diverse diatoms may invoke alternative strategies when dealing with identical changes in their environment. We report here several mechanisms used distinctly by coastal or oceanic diatom communities as well as numerous taxa-specific strategies for coping with Fe stress and rearranging nutrient metabolism following Fe enrichment.

Influence of diatoms on copepod reproduction. III. Consequences of abnormal oocyte maturation on reproductive factors in Calanus helgolandicus - S. A. Poulet; A. Cueff; T. Wichard; J. Marchetti; C. Dancie; G. Pohnert (Marine Biology, 2007)

In vitro antimicrobial activity of moxifloxacin against bacterial strains isolated from blood of neutropenic cancer patients - A. Cometta; O. Marchetti; T. Calandra; J. Bille; W. V. Kern; S. Zinner (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

A Strategy for Mapping the Heterochromatin of Chromosome 2 of Drosophila Melanogaster - Jiro C. Yasuhara; Marcella Marchetti; Laura Fanti; Sergio Pimpinelli; Barbara T. Wakimoto (Genetica, 2003)

Meiotic Chromosomes as Templates for Microdissection - Allen T. Christian; Melissa S. Pattee; Francesco Marchetti (Chromosome Research, 2002)